A record of thanatological type behaviour in spotted hyaenas, Crocuta crocuta (Erxleben, 1777) - Terry-Lee Honiball; Jan Adriaan Venter (Tropical Zoology, 2024)
We note thanatological behavioural displays by clan members of a deceased spotted hyaena, Crocuta crocuta (Erxleben, 1777) in a fenced reserve. A matriarch had a lethal altercation with lions, Panthera leo (Linnæus 1758), on 10.V.2022. The carcass was monitored with a camera trap that recorded videos until the carcass was completely decayed. Four instances of clan members were recorded observing and sniffing the genitalia of the deceased hyaena over a period of six days. Within one month, the clan killed the deceased’s cubs and moved their den location. We recommend further research be conducted into thanatological behaviours of spotted hyaenas as these behaviours could affect ethical considerations of management practices.